2010
DOI: 10.1021/jp1028195
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Charge Separation in Supramolecular Phthalocyanine−Multifullerene Conjugates Assembled by Crown Ether-Alkyl Ammonium Cation Interactions

Abstract: Self-assembled phthalocyanine-multifullerene donor-acceptor conjugates have been formed by crown ether-ammonium cation dipole-ion binding strategy to probe the photochemical charge separation. To achieve this, phthalocyanine is functionalized to possess four 18-crown-6 moieties on the macrocycle periphery, whereas fullerene is functionalized to possess an alkyl ammonium cation of short and long chain lengths. Stable donor-acceptor conjugates accommodating multifullerene entities have been obtained by the crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 84 publications
2
23
0
Order By: Relevance
“…In contrast, the unsubstituted cerium sandwich complex, CePc 2 , which is known to contain a tetravalent (Ce 4+ ) cation, displays no appreciable absorption intensity in the 500 nm spectral region. 34,36 On the basis of this comparison, as well as other considerations, the authors concluded that in solution the Ce 4+ oxidation state dominates for the Ce(15c5Pc) 2 complex, but upon the formation of monolayers, IET leads to the Ce 3+ oxidation state predominating.…”
Section: Intramolecular Et Systemsmentioning
confidence: 90%
“…In contrast, the unsubstituted cerium sandwich complex, CePc 2 , which is known to contain a tetravalent (Ce 4+ ) cation, displays no appreciable absorption intensity in the 500 nm spectral region. 34,36 On the basis of this comparison, as well as other considerations, the authors concluded that in solution the Ce 4+ oxidation state dominates for the Ce(15c5Pc) 2 complex, but upon the formation of monolayers, IET leads to the Ce 3+ oxidation state predominating.…”
Section: Intramolecular Et Systemsmentioning
confidence: 90%
“…An example is shown for ZnPc with multiple crown ethers, such as (crown) 4 ZnPc. Thus, the C 60 spheres with inclusion of −NH 3 + cannot approach the ZnPc‐surface (Figure a), which contrasts with (crown)ZnP approaching the C 60 sphere (Figure a, right). In the ns‐transient absorption spectra (Figure b), the lower intensity of the 700 nm band of 3 C 60 * supports the higher yield of complex formation, since the absorption intensity at 700 nm is a measure of uncomplexed C 60 .…”
Section: Fullerenes and Functionalized Fullerenesmentioning
confidence: 94%
“…Since then, molecular systems that exhibit bista bility-the ability to exist in two different electronic states and change their electronic state upon the effect of external actions-have attracted especial attention of researchers. The continuing interest in processes of reversible intramolecular electron transfer exists because these processes appear promising as a basis for develop ment of molecular sensors and nanosized devices for recording and storage of information [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Inter and Intramolecularmentioning
confidence: 99%
“…Presently, such effects as changes in the microenvi ronment (solvent replacement) [23,24,31,43] and thermal [27,28,33,[43][44][45] and magnetic and photo physical [26,30,32,38,39,[46][47][48] effects are used most widely as external controlling signals. Some separate works that describe the processes of redox isomerization in a 3D system under the influ ence of external pressure [49,50] deserve special atten tion.…”
Section: Inter and Intramolecularmentioning
confidence: 99%